Eye removal surgical techniques - M.B. Gushсhina; N.S. Yuzhakova; N.A. Gavrilova; T.S. Kondratenko (РМЖ "Клиническая офтальмология")
M.B. Gushchina1, N.S. Yuzhakova2, N.A. Gavrilova2, T.S. Kondratenko3 1Central Research Institute of Dental and Maxillofacial Surgery, Moscow, Russian Federation 2A.I. Evdokimov Moscow University of Medicine and Dentistry, Moscow, Russian Federation 3Goldberg-Klinik Kelheim GmbH, Kelheim, Germany About 12.000 eye removal surgeries are performed in Russian Federation every year. More than 50% of these patients are young working age individuals. Two major techniques of eye removal are used in clinical practice, i.e., evisceration and enucleation. However, systematic approach to the choice of surgical technique in certain clinical circumstances is not developed yet. This paper addresses foreign and domestic published data, indications and contraindications to evisceration and enucleation considering potential complications, their advantages and disadvantages depending on clinical situation. It was demonstrated that minimal risks of tumor cell dissemination and sympathetic ophthalmia as well as the possibility to perform detailed morphology of excised tissues are the advantages of enucleation. However, enucleation is associated with higher risks of postoperative complications resulting from orbital implant exposure. Considering this, it is important to select proper size-, construction-, and biocompatibility-matched orbital implant when choosing enucleation as an eye removal surgical technique. Keywords: enucleation, evisceration, orbital implant, stump, artificial eye, sympathetic ophthalmia, anophthalmic socket syndrome, implant exposure. For citation: Gushchina M.B., Yuzhakova N.S., Gavrilova N.A., Kondratenko T.S. Eye removal surgical techniques. Russian Journal of Clinical Ophthalmology. 2020;20(1):–48. DOI: 10.32364/2311-7729-2020-20-1-37-48.